First and second generation antipsychotics differentially affect structural and functional properties of rat hippocampal neuron synapses. (19th November 2016) - Gottschling, Christine; Geissler, Maren; Springer, Gianna; Wolf, Rainer; Juckel, Georg; Faissner, Andreas
Highlights: A neuron-glia insert co-culture model was used to monitor synapse plasticity. The co-culture serves to model chronic treatment with psychopharmacological drugs. Distinct antipsychotics have differential effects on synapse formation. Resulting neuronal networks show differences of synaptic activity. Abstract: The therapy of patients suffering the psychiatric disorder schizophrenia requires the usage of antipsychotic drugs that are classified into two different groups, the first-generation (FGAs) and the second-generation antipsychotics (SGAs). This study compares the effects of the two FGAs haloperidol and flupentixol with those of the SGA olanzapine on synapse formation and synaptic activity of embryonic rat hippocampal neurons. To this end, the development of perineuronal nets (PNNs), the formation of synapses and the resulting spontaneous network activity under control and treatment conditions were studied using an indirect co-culture system of neurons and astrocytes in completely defined media. The number and extent of PNNs that consist of extracellular matrix superstructures surrounding synapses was not altered in hippocampal neurons by exposure to antipsychotic drugs. In contrast treatment of hippocampal neurons with haloperidol led to a slight decrease whereas olanzapine induced a significant increase of the number of structural synapses after 13 days. This differential effect concerning synapse numbers was also reflected in the spontaneous activity of neuronal networks, as monitored on multielectrode arrays (MEAs). In that context, application of haloperidol reduced while olanzapine significantly enhanced network activity. Unexpectedly, flupentixol that is regarded as an FGA caused similar effects than the SGA olanzapine in that it augmented synapse number as well as network activity. Our pilot study provides a proof of concept that the neuron-astrocyte co-culture model can be used to investigate the impact of antipsychotics on pivotal parameters of neuronal cell biology. Thereby, it may support the comparative analysis of antipsychotics applied in the therapy of schizophrenia.